The Role of Value Alignment as a Mediator Between Halal Products and Repurchase Intention - Sylvani, Aurora Bella; Djastuti, Indi (Research Horizon, 2024)
The purpose of this study is to overcome the inconsistency of research results between Halal Products and Repurchase Intention, so this study uses the role of value congruence as a mediator between halal products and repurchase intention in Wardah cosmetic customers in Central Java. The variables of this study are Halal Products (HP) as an antecedent, Value Congruence (VC) as a mediator, and Repurchase Intention (RI) therefore. The sampling technique in this study is purposive sampling. The sample used in this study was 240 respondents. The data in this study will be analyzed using a structural equation model (SEM-PLS) using the Smart PLS 3 program. The results of this study found that Value Congruence can mediate between Halal Products and Repurchase Intention. Other findings from this study are that Halal Products have a direct positive effect on Repurchase Intention, Halal Products have a direct positive effect on Value Congruence, and Value Congruence has a direct positive effect on Repurchase Intention. This study is expected to contribute to the Self-Congruence Theory approach. In addition, the results of this study also offer important insights for halal product managers.